Rationalities of Z-category shares in Dhaka stock exchange: are they in financial distress risk? - Chowdhury, Anup; Barua, Suborna (BRAC University, 2010)
Financial distress is a situation where a firm’s operating cash flows are not sufficient to satisfy current obligations and the firm is forced to take corrective actions, and a firm in financial distress may also face bankruptcy or liquidation to meet its liabilities. Financial distress can be caused by losses, dividend reduction or bankruptcy. A good way to measure the possibility of bankruptcy is to use Z score model (Altman, 1968). This paper uses the Z score model to predict risk of financial distress of Z category companies listed in Dhaka Stock Exchange (DSE). Results suggest that five of fifty three companies are out of danger while seven of those are in the gray area. Evidently, forty one of the companies are operating with high distress risk as suggested by the model result. Therefore ninety percent of the companies are suffering from financial distress risk due to very poor management capability and operating inefficiency although its reflection to the stock price is absent from the market in many instances. The Altman’s Z score, model though may not be fully applicable for companies in Bangladesh, yet proves its strong validity and correctness in predicting distressful status of the Z category companies.